Tetracaine from urethral ointment causes false positive amphetamine results by immunoassay. (3rd June 2021) - Wijngaard, Robin; Parra-Robert, Marina; Marés, Lourdes; Escalante, Anna; Salgado, Emilio; González-de-la-Presa, Bernardino; To-Figueras, Jordi; Brunet, Mercè
Abstract: Background: Amphetamine urine drug screening by immunoassay is prone to cross-react with other compounds leading to false positive results. Tetracaine is a local anesthetic drug used in the clinical setting as an ointment during urinary catheterization. In our laboratory, tetracaine is often detected by gas chromatography-mass spectrometry in the urine of patients admitted in the emergency department with false positive amphetamine results. The objectives of this study were to investigate if there was cross-reactivity to tetracaine in an amphetamine immunoassay and to retrospectively evaluate the potential contribution of tetracaine to false positive amphetamine results. Methods: An interference study was conducted using negative urine samples spiked with increasing concentrations of tetracaine hydrochloride and analyzed with the CEDIA Amphetamine/Ecstasy immunoassay. Retrospectively, urine samples of patients which yielded positive amphetamine immunoassay results and were analyzed by gas chromatography-mass spectrometry were reviewed ( n  = 417). The presence of tetracaine and/or other drugs by gas chromatography-mass spectrometry were gathered. Results: Tetracaine caused false positive amphetamine results by immunoassay (cut-off 1000 µg/L) with a concentration of above 40 mg/L. Retrospective analysis of all positive amphetamine immunoassay samples showed that in 45 out of the 417 (10.8%) urine samples no amphetamine-like derivative was identified by gas chromatography - mass spectrometry. In 37 out of 45 (82.2%) of these false positive cases tetracaine was detected, of whom 59.5% (22/37) had an estimated tetracaine concentration of ≥40 mg/L. Conclusions: This study confirmed the interference of tetracaine in the CEDIA Amphetamine/Ecstasy immunoassay and that tetracaine may have contributed to around 80% of the false positive amphetamine cases in the urine samples of patients admitted to the emergency department at our institution.